PERSEPSI MASYARAKAT TERHADAP GALIAN BATU C (AQUARI) DI KELURAHAN PASIR SIALANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Maizurah "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted at Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar. Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar The purpose of this study is to determine the socio-economic changes of the community with the Land at Galian Batu C (Aquari) di Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar. The focus of this research is to analyze people's perception of land at Galian Batu C (Aquari) di Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar. The sampling technique used is Simple Random Sampling. the minimum sample in this study was 96 respondents. The author uses descriptive quantitative methods and Instruments data are questionnaires, interviews and documentation.Research conducted, the authors found that there are three changes that occur in the community with the land galian C at Kelurahan Pasir Sialang, namely: a change in the level of basic income felt by as many as 75% of respondents, changes to employment opportunities perceived by as many as 69.7% of respondents and changes to access development accommodation perceived by as much as 25%. It also found some public perceptions about the activity of excavated land c that is, the source of community income for the community, the availability of new jobs, damaging the surrounding environment and assisting the community accommodation. Keywords: Perception, Mining, Galian C, Society